2002
DOI: 10.1038/sj.cgt.7700482
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppression effect using NK4, a molecule acting as an antagonist of HGF, on human gastric carcinomas

Abstract: Hepatocyte growth factor ( HGF ) is involved in malignant behavior of cancers as a mediator of tumor-stromal interactions, facilitating tumor invasion and metastasis. We have investigated whether a blockade of HGF using recombinant NK4, an HGF antagonist, would lead to growth inhibition of the human gastric carcinoma cell line, TMK1. To evaluate the function of endogenous NK4 and investigate its potential inhibitory effect, TMK1 cells were transfected with NK4 plasmid. After selection, NK4-expressing cells ( T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…39 So far, NK4 gene therapy has demonstrated efficacy in tumor models in which the involvement of the HGF-cMET signaling pathway in pathogenesis has been clearly established. [8][9][10][11][12][13][14][15][16][17][18][19][20] Based on the multifunctional properties of NK4 on various growth factors, 3,4,12,40 we propose that NK4 gene therapy would have therapeutic value for a wider range of tumors than only cMET overexpressing carcinomas. However, application of NK4 gene therapy to specific tumor types such as HCC for which the effect of the HGF-cMET signaling is less explicit or may even be inhibitory on carcinogenesis [32][33][34] needed further assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 So far, NK4 gene therapy has demonstrated efficacy in tumor models in which the involvement of the HGF-cMET signaling pathway in pathogenesis has been clearly established. [8][9][10][11][12][13][14][15][16][17][18][19][20] Based on the multifunctional properties of NK4 on various growth factors, 3,4,12,40 we propose that NK4 gene therapy would have therapeutic value for a wider range of tumors than only cMET overexpressing carcinomas. However, application of NK4 gene therapy to specific tumor types such as HCC for which the effect of the HGF-cMET signaling is less explicit or may even be inhibitory on carcinogenesis [32][33][34] needed further assessment.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] NK4, which consists of the N-terminal hairpin domain and the four subsequent kringle domains of HGF, competitively inhibits the multiple biological activities of HGF through binding to cMET and is suggested to have a broad antiangiogenic activity through its kringle domain structure. 3,4,7 Previous in vivo studies confirmed therapeutic efficacy of NK4 gene therapy for glioblastoma, prostate, breast, gastric, pancreatic, gall bladder and colon cancers [8][9][10][11][12][13][14][15][16][17][18][19][20] and recommended further preclinical evaluation of NK4 gene therapy as anticancer agent. However, NK4 gene therapy for treatment of HCC could be argued against because the antitumor effects of NK4 in part rely on its antagonistic activity to HGF 3 and the role of the HGF-cMET system in hepatocarcinogenesis has not been clearly established.…”
mentioning
confidence: 99%
“…Thus, NK4 may also have utility for anti-tumor immunotherapy. There is now ample evidence that NK4 is useful for the inhibition of growth, invasion and metastasis in various types of tumors, such as gastric carcinoma (Hirao et al, 2002), pancreas cancer (Tomioka et al, 2001), prostate cancer (Davies et al, 2003), multiple myeloma (Du et al, 2007) and melanoma (Kishi et al, 2009) (Table-1). These results support our hypothesis that HGF is a key determinant of tumor malignancy (Matsumoto et al, 1996b Adeno-NK4, adenoviral vector carrying NK4 cDNA; r-NK4, recombinant NK4 protein; sc, subcutaneous; iv, intravenous; ip, intraperitoneal; im, intramuscular; DC, dendritic cells; and CTL, cytotoxic T lymphocytes.…”
Section: Therapy Combining Nk4 With Other Treatmentsmentioning
confidence: 99%
“…The antitumor effect was related to a decrease in density of microvessels in tumors. NK4, a hepatocyte growth factor (HGF) antagonist, is another antiangiogenic factor that has been demonstrated to exhibit antitumor activity in many tumors, too [92][93][94][95]. NK4 consists of the Nterminal hairpin domain and the four subsequent kringle domain of HGF.…”
Section: Inhibition Of Angiogenesismentioning
confidence: 99%